PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GAME PUZZLE PADA MATERI SISTEM KOMPUTER KELAS X A MA DARUL HIKMAH TULUNGAGUNG - Nur Huda Alwi, M.; Dwi Pamungkas, Bian; Panggayuh, Vertika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was prompted by ICT learning at MA Darul Hikmah Tulungagung thatremained dominated by lectures and printed worksheets, while students hadrestricted access to personal digital devices under boarding-school regulations andthe computer laboratory was not used optimally for daily instruction. The studyaimed to develop and determine the feasibility of an offline puzzle game-basedlearning medium for the Computer Systems topic in Grade X. The research used theResearch and Development method with the ADDIE model, comprising analysis,design, development, implementation, and evaluation. The product was built as aWindows desktop application using JavaScript, React, Vite, Electron, dnd-kit,Howler.js, and Lottie. Data were collected through observation, teacher interviews,expert-validation questionnaires, and student-response questionnaires. The mediaexpert score increased from 94.17% in the first validation to 98.30% after revision,while the subject-matter expert score reached 100%. The small-group trial involvingfive students obtained 99.88%, and the large-group trial involving twenty studentsobtained 99.63%. All scores were classified as highly valid and highly feasible. Thedeveloped medium provides material, leveled puzzle challenges, audio-visualfeedback, and evaluation features that can operate offline in the school laboratory.The findings demonstrate product feasibility, but they do not yet establish itseffectiveness in improving learning outcomes.